Designing Lesson Plan Based on Critical Thinking for Language Classes - Norwanto Norwanto (IAIN Salatiga, 2011)
Critical thinking includes a process of reasoning in thinking as stated by some scholars. In the process, there is universal standard to follow: clarity, accuracy, precision, relevance, depth, breadth, logic, and fairness. In language classes, critical thinking creates active classes. To bring critical thinking to classes, Bloom’s Taxonomy and critical thinking strategies can be working definition in order critical thinking to be applied to pedagogical materials in a practical way. Steps for critical thinking teaching includes five steps: (1) determining learning objectives, (2) teaching through questioning, (3) practicing before assessing, (4) reviewing, refining, and improving, and (5) providing feedback and assessment of learning. A lesson plan should reflect these five steps.Keywords: Critical Thinking; Language Teaching; Lesson Plan; Bloom’s Taxonomy; Critical Thinking Strategies